An empirical investigation of the antecedents and performance outcomes of export innovativeness. Issue 4 (August 2017) - Makri, Katerina; Theodosiou, Marios; Katsikea, Evangelia
Highlights: Export innovativeness can be inspired and spurred through decentralized structures within the exporting firm. Export market orientation as a strategic approach provides managers with special skills and knowledge concerning the foreign market and enables them to come up with innovative solutions to exporting challenges. Under conditions of high market dynamism and competitiveness, foreign customers needs change constantly and emphasis should be placed on the offering of innovative products. Abstract: The present study develops and empirically tests a conceptual model of the organizational, strategic, and environmental drivers of export innovativeness. The relationship between export innovativeness and export performance is also examined. Using data collected from 168 small- and medium-sized direct exporters, we find that decentralization in decision making, export market orientation, information exchange and export market dynamism have a significant influence on exporting firms' degree of innovativeness. Furthermore, export innovativeness has a significant positive effect on export performance. Several theoretical and managerial implications are derived from these findings. Directions for future research are also provided.